Cheaper by the dozen - Levy, Shawn (Pasig City : Viva Video, 2003)
Comedy superstar Steve Martin (Bringing Down the House) and TVfilm favorite Bonnie Hunt (Jerry Maguire)" couldn't be more likeable" (Leonard Martin, Hot Ticket) in this hilarious tale of two loving parents trying to manage careers and a household - amid the chaos of raising twelve rambunctious kids. with a crowd-pleasing supporting cast, including rising young stars hillary Duff, Tom Welling and Piper Perabo, this heartwarming hit comedy delivers super-sized fun and laughs by the dozen